Wavelet-based numerical solution for MHD boundary-layer flow due to stretching sheet - Karkera, Harinakshi; Katagi, Nagaraj N. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a two-dimensional steady flow of a viscous fluid due to a stretching sheet in the presence of a magnetic field is considered. We proposed two new numerical schemes based on the Haar wavelet coupled with a collocation approach and quasi-linearization process for solving the Falkner-Skan equation representing the governing problem.
Keywords: MHD flow; boundary layer; quasi-linearization; Haar wavelets